Asthma academy: A student nurse‐led telehealth education program for low‐income family caregivers of children with asthma. Issue 2 (16th December 2021) - Foronda, Cynthia; Prather, Susan; Snowden, Kenya; Gonzalez, Juan M.; Gattamorta, Karina A.; Lee, Jiye; Gonzalez, Juan E.; Cardenas, Monica
Abstract: Aims: The aims of the Asthma Academy study were to (1) evaluate the telehealth performance of DNP students, (2) evaluate the perceived learning experience of DNP students and (3) investigate whether an association exists related to student performance and family caregiver outcomes. Design: A descriptive study was conducted with doctor of nursing practice students. Methods: Students conducted telehealth visits to help family caregivers of children with asthma and were rated on their performance by two faculty members using a rubric. Student perception data were gathered via survey. Results: Out of a total possible score of 15 points, the mean telehealth performance score of students was 13.38 points. Students indicated the telehealth experience was valuable and that they were satisfied with their learning. This model of leveraging telehealth to bridge nursing students to the community may be adapted to help family caregivers of children with various disease foci.